Endoplasmic reticulum contains a common, abundant calcium-binding glycoprotein, endoplasmin - Koch, G.; Smith, M.; Macer, D.; Webster, P.; Mortara, R. (Company of Biologists, 1986)
The most abundant protein in microsomal membrane preparations from mammalian cells has been identified as a 100 × 103Mr concanavalin A-binding glycoprotein. The glycosyl moiety of the glycoprotein is completely sensitive to endoglycosidase H, suggesting a predominantly endoplasmic reticulum localization in the cell. Using a monospecific antibody it was shown by binding and immunofluorescence studies that the glycoprotein is intracellular. Immunoelectron microscopy showed that the glycoprotein was at least 100 times more concentrated in the endoplasmic reticulum than in any other cellular organelle. It was found to be substantially overexpressed in cells and tissues rich in endoplasmic reticulum. Since it is the major common protein component associated with the endoplasmic reticulum we refer to it as endoplasmin. Calcium-binding studies show that endoplasmin is a major calcium-binding protein in cells, suggesting that at least one of its roles might be in the calcium-storage function of the endoplasmic reticulum. The amino-terminal sequence of endoplasmin is identical to that of a 100 × 103Mr stress-related protein.